(untitled) (Research, Society and Development, 2024)
Introduction: Pseudoaneurysm is one of the main complication of vascular neck trauma and it has been historically underestimated because patients with non-catastrophic injuries may not show symptoms until several years after the trauma, but it can result in catastrophic sequelae. Objective: The objective of this article is to present a case report on pseudoanerysm of the common carotid artery due to penetrating trauma. Case report: Male patient, 22 years old with left common carotid artery pseudoaaneurysm due to gunshot two years before. He presented progressive left-sided cervical mass and previous history of two cerebrovascular accidents, resulting in right hemiparesis and dysarthria sequelae. The patient was submitted to open surgical repair and was discharged on the fourth day postoperative in good condition. Conclusion: Our patient was young and had an easily accessible lesion, therefore, we felt that the most durable approach would be open surgical reconstruction with excellent immediate result.